Selecting Differentiated Costs between primary PCI and Thrombolytic Therapy using Hybrid of Genetic Algorithm and Decision Tree Approach - Masoumeh Saeedian; MohammadMehdi Sepehri; Hassan Aghajani; Toktam Khatibi (Tehran University of Medical Sciences, 2015)
Background: Myocardial Infarction (MI) is the most common cause of death in developed and developing countries. Based on World Health Organization prediction, MI will be the leading cause of death in the world up to 2020. The main goal of acute myocardial infarction therapy is reperfusion which is performed by two treatment approaches, although these two methods use for unique complication treatment but they are different in treatment cost and quality; Since the costs of health care is growing, this study aimed at identifying affected differentiated costs among patients with acute MI with the purpose of providing a framework to compare two treatment methods. Materials and Methods: In presented model in current study, with the purpose of select affecting cost attributes utilized hybrid of Genetic algorithm and decision tree approach as a new method and compare its result using random method. Results: Study result presented classifies error reduction up to 0.2 compare with random method error. Then, based on selected attributes, presented a framework comparing two treatment methods. Also, in the majority of direct cost and total cost, Primary Angioplasty was cost effective more than Thrombolytic Therapy, but in indirect cost, we achieved some results dissimilar to physicianschr('39') expected results such as kidney failure. Conclusion: Suggested approach in this research can be a guidance to physicians and insurances institutes in acute myocardial infarction treatment policies.